PERSPECTIVES OF LIME PRODUCTION DEVELOPMENT AT BELORUSSIAN METALLURGICAL WORKS - A. G. Kozhevnikov (Литьë и металлургия)
The perspectives of development of lime production at Belorussian metallurgical works are examined.